First high resolution interferometric observation of a solar prominence with ALMA. Issue 1 (7th March 2022) - Labrosse, Nicolas; Rodger, Andrew S; Radziszewski, Krzysztof; Rudawy, Paweł; Antolin, Patrick; Fletcher, Lyndsay; Levens, Peter J; Peat, Aaron W; Schmieder, Brigitte; Simões, Paulo J A
ABSTRACT: We present the first observation of a solar prominence at 84 − 116 GHz using the high resolution interferometric imaging of ALMA. Simultaneous observations in Hα from Białkaw Observatory and with SDO/AIA reveal similar prominence morphology to the ALMA observation. The contribution functions of 3 mm and Hα emission are shown to have significant overlap across a range of gas pressures. We estimate the maximum millimetre-continuum optical thickness to be τ3mm ≈ 2, and the brightness temperature from the observed Hα intensity. The brightness temperature measured by ALMA is ∼6000 – 7000 K in the prominence spine, which correlates well with the estimated brightness temperature for a kinetic temperature of 8000 K.